2014
DOI: 10.3109/0142159x.2014.956057
|View full text |Cite
|
Sign up to set email alerts
|

Preserving third year medical students’ empathy and enhancing self-reflection using small group “virtual hangout” technology

Abstract: This study supports previous findings showing that students benefit from peer groups and discussion in a safe environment, which may include the use of a virtual group video platform.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
87
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(88 citation statements)
references
References 19 publications
1
87
0
Order By: Relevance
“…20 The authors suggested the process of reflective writing should be considered in any curricula, as this approach was successful at developing empathy. 18 Self-reflection activities have been successfully introduced into curricula through a variety of formats, including group peer discussions 21 and mindfulness training. 22 Because the underlying principles of traditional and digital empathy constructs are the same, both communications training and self-reflection activities could theoretically prompt learners to question and examine their interactions in the online world.…”
Section: Teaching Digital Empathymentioning
confidence: 99%
“…20 The authors suggested the process of reflective writing should be considered in any curricula, as this approach was successful at developing empathy. 18 Self-reflection activities have been successfully introduced into curricula through a variety of formats, including group peer discussions 21 and mindfulness training. 22 Because the underlying principles of traditional and digital empathy constructs are the same, both communications training and self-reflection activities could theoretically prompt learners to question and examine their interactions in the online world.…”
Section: Teaching Digital Empathymentioning
confidence: 99%
“…For this to be achievable staff members may need to have some form of IT training as they are not as apt at social media use as students (Duke et al, 2014). Brisson et al's (2015) study focuses on the mismatch between lecturer and student.…”
Section: Role Of Facultymentioning
confidence: 99%
“…The Liaison Committee on Medical Education (LCME) in the USA point to core professional qualities such as compassion and integrity that must be developed during a student's time at medical school (Duke et al, 2014). Social media can be used as a tool for training professionalism (Duke et al, 2014;Hennessy et al, 2016).…”
Section: Professionalismmentioning
confidence: 99%
See 1 more Smart Citation
“…20 The lack of impact of the curriculum on residents' empathy and resilience is inconsistent with the literature. [21][22][23] It is likely that sample size and poor completion rates across time contributed to the nonsignificant changes, as only a minority of residents completed all 3 assessments. It also is possible that the length of exposure to the curriculum was too brief, or the measures used were not sufficiently sensitive to detect changes.…”
Section: Discussionmentioning
confidence: 99%